THE SPANISH MOOD/SUBORDINATION/REFERENCE INTERFACE - Gregory, Amy E. (International Journal of English Studies, 2009)
This study deals with the discourse function of the Spanish subjunctive mood. Traditional approaches focus on its semantics, invoking the notions of volition, doubt, negation, and emotion while maintaining the importance of the clause’s subordinate status and change of subject from matrix verb to subordinate verb. Notwithstanding, thirty years of linguistic research on the Spanish mood contrast have given rise to the descriptors ± assertion: indicative is +assertive while subjunctive is -assertive. Although these descriptors are appropriate, viewing the subjunctive mood as a discourse cohesive device makes apparent the true nature of the mood contrast. Anaphoric, exophoric, and cataphoric features of languages refer to antecedents, elements of the physical context, or foreshadowed events/information, respectively. This article proposes a mechanism by which Spanish subjunctive clauses fulfill all three functions, circumscribing the Spanish mood contrast within the language’s deictic system, and suggests avenues for future research.